Demonstrationszug mit Banner "Rüstung für (Frieden?) ist wie Schnaps gegen Alkoholismus KJV"
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Kommunismus politischer Rahmen;politisches Leben (allgemein);politisches Leben (speziell);Demonstration